MEMPERTIMBANGKAN HERMENEUTIK GADAMER SEBAGAI METODE TAFSIR (Telaah Terhadap Teori Asimilasi Horison) - Moh Alwy Amru Ghozali; Umi Kalsum (IAIN Ponorogo, 2020)
Abstrak: Debate about the use of hermeneutics in the study of the Qur'an is still often raised. This article tries to build an argument for the possibility of integrating the horizon assimilation theory in Gadamer hermeneutics into the science of interpretation (ilmu tafsir). By using the comparative-descriptive-analytical method, the author sees that the theory can enrich the interpretation method. Conventional interpretation using the method of tahlili, ijmali, muqaran, and maudlu'i is still around the text, so that the interpretation becomes less actual and contextual. The marriage between the horizon gadamer assimilation theory and the interpretation method can cover up the shortcomings, and give birth to what the writer call